Corporate Governance in Malaysia: Issues and Challenges (Isu dan Cabaran Tadbir Urus Korporat di Malaysia) - Nina Nurasyekin Zulkefli; SM Abdul Quddus (Journal of Islam in Asia (E-ISSN 2289-8077), 2019)
Corporate governance is a set of structural process that includes the actions of directing and controlling by the authorized board of directors. In Malaysia, corporate governance is directly under the involvement of the Ministry of Finance, Bursa Malaysia, and Securities Commissions (SC) and Registrar of Company. A good reform of corporate governance in Malaysia is essential to enhance the quality of corporate governance practices after the Asian Financial Crisis 1997. The statistic shows that the low number of Malaysian companies adhered to good corporate governance practices. This poses a question of the extent to what issues and challenges faced by the Malaysian companies reluctantly to adopt a good practice of corporate governance. Hence, the Malaysian government has initiatively introduced Malaysia Code of Corporate Governance (MCCG) as a new code and rules for solving the problems of corporate governance. This study is important to ensure better management of corporate governance of companies in Malaysia, accountability, integrity, and transparency, thereby ensuring the survival of Malaysian corporate governance institutions around the world. The paper uses a qualitative approach. The findings from this study highlight that the introduction of MCCG is tantamount to solve the underpinning problems of the corporate governance system. Keywords: Corporate governance, Malaysia, MCCG, Asian Financial Crisis. Abstrak Tadbir urus korporat adalah satu set proses struktur yang merangkumi sistem penyeliaan oleh lembaga pengarah yang diberi kuasa. Di Malaysia, tadbir urus korporat adalah di bawah penglibatan Kementerian Kewangan, Bursa Malaysia, dan Suruhanjaya Sekuriti (SC) dan Suruhanjaya Syarikat Malaysia. Pembaharuan tadbir urus korporat yang baik di Malaysia adalah penting untuk meningkatkan kualiti amalan tadbir urus korporat selepas Krisis Kewangan Asia 1997. Statistik menunjukkan bahawa bilangan syarikat Malaysia yang rendah dalam mematuhi amalan tadbir urus korporat yang baik. Ini menimbulkan persoalan sejauh mana isu dan cabaran yang dihadapi oleh syarikat-syarikat di Malaysia yang enggan mengamalkan amalan tadbir urus korporat yang baik. Justeru, kerajaan Malaysia telah memperkenalkan Kod Tadbir Urus Korporat Malaysia (MCCG) sebagai kod baru dan peraturan untuk menyelesaikan masalah tadbir urus korporat. Kajian ini penting untuk memastikan pengurusan tadbir urus korporat yang lebih baik di Malaysia, akauntabiliti, integriti dan ketelusan, serta seterusnya memastikan kelangsungan institusi tadbir korporat Malaysia di seluruh dunia. Kaedah kajian adalah menggunakan pendekatan kualitatif. Dapatan kajian ini menunjukkan bahawa pengenalan MCCG adalah penting untuk menyelesaikan masalah asas sistem tadbir urus korporat. Kata Kunci: Tadbir Urus Korporat, Malaysia, MCCG, Krisis Kewangan Asia.